Prevalence and antibiotic susceptibility of Aeromonas hydrophila isolated from freshwater fishes - Halima Sarder; Nusrat Jahan Punom; Tahsin Khan; Mihir Lal Saha; Shankar Chandra Mandal; Mohammad Shamsur Rahman (Journal of Fisheries, 2016)
Aeromonas hydrophila is an opportunistic microorganism. It is a secondary biological agent that contributes to the occurrence of fish diseases and its deterioration. This research was undertaken to determine the prevalence of A. hydrophila in some freshwater fishes collected from three different fish markets of Dhaka City and to test their antibiotic susceptibility. Total bacterial count and total aeromonas on different aeromonas selective media were enumerated using serial dilution technique. Bacterial isolates were characterized to identify A. hydrophila using biochemical tests and with comparison to reference strain (ATCC 7966). The lowest Aeromonas count was detected to be 2.83±0.40×102 cfu/g in Anabas testudineus and the highest was 1.03±0.153×103 cfu/g in Oreochromis mossambicus. On market basis highest aeromonas count was found in Anando Bazar (8.10±1.09×102 cfu/g) and lowest in Hatirpool Bazar (5.63±0.90×102 cfu/g) with no significant difference. Maximum susceptibility to amikacin and gentamicin was observed whereas all of the isolates were found resistant to a commonly used antibiotic amoxycillin. The obtained results point that antimicrobial susceptibility was more or less similar regardless of the origin of the samples collected. All the fishes investigated in this study contained A. hydrophila in their different organs.